Experiment Study and Dynamic Simulation Analysis of Transmission Performance of High-performance Magnetic Gear - Yang Chaojun; Zhang Xiuwen; Ji Chenglong; Zhang Youjing; Yuan Airen (Jixie chuandong, 2016)
Aiming at the high-performance magnetic gear with 7 pole pairs of permanent magnet inner rotor and 15 pole pairs of permanent magnet outer rotor,in order to study the working principle and transmission performance,the three different running manners are discussed,their gear ratios relation are derived,and the relationship among efficiencies,torques and gear ratios are also derived. When the speeds is lower,the efficiency is almost equal to 1,thus the out torque is equal to the input torque times its gear ratio. Also,the three different running manners under lower speeds are dynamically simulated by using the finite element analysis software,and the influence of different loads on torques is obtained. Then,the input torque and output torque are measured under different loads by transmission experiment platform respectively. The results show that the input torque increases linearly with the increase of the output torque,and the ratio of output and input torque is equal to the gear ratio. All these can be used to estimate the dynamic torque when the transmission ratio is given.